Adenosine Receptor Agonists Increase the Inhibition of Platelet Function by P2Y12 Antagonists in a cAMP- and Calcium-Dependent Manner - Nina Wolska; Hassan Kassassir; Boguslawa Luzak; Cezary Watala; Marcin Rozalski (MDPI AG, 2020)
We have shown previously that platelet activity can be lowered through the simultaneous inhibition of P2Y12 receptor and activation of adenosine receptors (AR). This work explores this concept by testing the antiplatelet potential of nine AR agonists in combination with P2Y12 receptor antagonists-cangrelor and prasugrel metabolite. A panel of in vitro methods was used to assess platelet viability, P-selectin expression, GPIIb-IIIa activation, fibrinogen binding, calcium ion mobilization, VASP-P level, and cAMP formation, utilizing whole blood or isolated platelets from healthy volunteers. The AR agonists demonstrated anti-platelet effects, but stimulated signaling pathways to varying degrees. AR agonists and P2Y12 antagonists reduced expression of both P-selectin and the activated form of GPIIb-IIIa on platelets; however, the combined systems (AR agonist + P2Y12 antagonist) demonstrated stronger effects. The antiplatelet effects of AR when combined with P2Y12 were more pronounced with regard to exogenous fibrinogen binding and calcium mobilization. The cAMP levels in both resting and ADPactivated platelets were increased by AR agonist treatment, and more so when combined with P2Y12 inhibitor. In conclusion, as AR agonists are fast-acting compounds, the methods detecting early activation events are more suitable for assessing their antiplatelet action. The exogenous fibrinogen binding, calcium mobilisation and cAMP level turned out to be sensitive markers for detecting the inhibition caused by AR agonists alone or in combination with P2Y12 receptor antagonists.